Molecular Dynamics Simulations Reveal the Interaction Fingerprint of Remdesivir Triphosphate Pivotal in Allosteric Regulation of SARS-CoV-2 RdRp - Srivastava, Mitul; Mittal, Lovika; Kumari, Anita; Asthana, Shailendra (Frontiers in Molecular Biosciences, 2021)
The COVID-19 pandemic has now strengthened its hold on human health and coronavirus’ lethal existence does not seem to be going away soon. In this regard, the optimization of reported information for understanding the mechanistic insights that facilitate the discovery towards new therapeutics is an unmet need. Remdesivir (RDV) is established to inhibit RNA-dependent RNA polymerase (RdRp) in distinct viral families including Ebola and SARS-CoV-2. Therefore, its derivatives have the potential to become a broad-spectrum antiviral agent effective against many other RNA viruses. In this study, we performed comparative analysis of RDV, RMP (RDV monophosphate), and RTP (RDV triphosphate) to undermine the inhibition mechanism caused by RTP as it is a metabolically active form of RDV. The MD results indicated that RTP rearranges itself from its initial RMP-pose at the catalytic site towards NTP entry site, however, RMP stays at the catalytic site. The thermodynamic profiling and free-energy analysis revealed that a stable pose of RTP at NTP entrance site seems critical to modulate the inhibition as its binding strength improved more than its initial RMP-pose obtained from docking at the catalytic site. We found that RTP not only occupies the residues K545, R553, and R555, essential to escorting NTP towards the catalytic site, but also interacts with other residues D618, P620, K621, R624, K798, and R836 that contribute significantly to its stability. From the interaction fingerprinting it is revealed that the RTP interact with basic and conserved residues that are detrimental for the RdRp activity, therefore it possibly perturbed the catalytic site and blocked the NTP entrance site considerably. Overall, we are highlighting the RTP binding pose and key residues that render the SARS-CoV-2 RdRp inactive, paving crucial insights towards the discovery of potent inhibitors.